2013
DOI: 10.1177/0036933013482638
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms do not predict colorectal cancer in an FOB screened population

Abstract: Half the FOB screen-positive patients had bowel symptoms. Symptoms in these patients had no correlation with an increased rate of neoplasia. The PPV for neoplasia is superior in symptomatic and asymptomatic screen-positive patients when compared to conventional urgent symptom-based referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…reported that 52% of Scottish FOBT-positive screening participants had CRC-related symptoms. 30 Ahmed et al. described 78% symptomatic FOBT-positive Scottish screening participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that 52% of Scottish FOBT-positive screening participants had CRC-related symptoms. 30 Ahmed et al. described 78% symptomatic FOBT-positive Scottish screening participants.…”
Section: Discussionmentioning
confidence: 99%
“…The two previous studies similarly assessed symptoms in a FOBT‐positive screening population and observed even higher proportions of symptomatic participants. Saldanha et al reported that 52% of Scottish FOBT‐positive screening participants had CRC‐related symptoms 30 . Ahmed et al described 78% symptomatic FOBT‐positive Scottish screening participants 31 .…”
Section: Discussionmentioning
confidence: 99%
“…17 In FOBT positive screening populations, the prevalence of bowel symptoms is reported to be between 47% and 78%. [18][19][20][21] Systematic reviews and meta-analyses provide evidence for an association between rectal bleeding and CRC in primary and secondary care, 3 4 22 while other 'alarm symptoms' such as change in bowel habits, abdominal pain and bloating have uncertain diagnostic value. 5 23 The usefulness of symptoms in predicting CRC or advanced adenomas in screening populations is contradictory.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…5 23 The usefulness of symptoms in predicting CRC or advanced adenomas in screening populations is contradictory. [17][18][19][20][21] In addition, there is limited attention on the detection rates among truly asymptomatic individuals in these screening populations.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Studies have suggested that large proportions of colorectal cancer screening participants have underlying symptoms [26][27][28] despite recommendations and campaigns for symptomatic individuals to visit their GP. Some of these symptoms can be considered 'low risk, but not no risk' [29] and are often self-limiting but in combination can indicate underlying disease [13,14].…”
Section: Predictorsmentioning
confidence: 99%